Simulation Study On Non-Homogenous System Of Non-Invasive ERT Using Comsol Multiphysics - Yasmin Abdul Wahab; Ruzairi Abdul Rahim; Mohd Hafiz Fazalul Rahiman; Leow Pei Ling; Suzzana Ridzuan Aw; Fazlul Rahman Mohd Yunus; Herlina Abdul Rahim; Naizatul Shima Fadzil; Mohd Zikrillah Zawahir; Muhammad Saiful Badri Mansor; Mohd Fadzli Abdul Sahib; Ling En Hong; et al. (Penerbit UTM Press, 2024)
Volume: 77 No: 17: Special Issue on Sensor Technology and Control System Applications Vol. 3